Fabrication defects and limitations of AlSi10Mg lattice structures manufactured by selective laser melting. (October 2021) - Ossola, Enrico; Shapiro, Andrew A; Pate, Andre; Firdosy, Samad; Brusa, Eugenio; Sesana, Raffaella
Additive manufacturing has enabled the production of lattice structures with tailored mechanical properties. However, process limitations still exist, affecting the quality of the struts, practically limiting sizes and types of printable unit cells. Typically, long, thin, unsupported horizontal struts exhibit large deviations from ideal geometries, due to high surface roughness and internal porosity. AlSi10Mg specimens were designed and fabricated by laser powder bed fusion to investigate the role of strut orientation, size, and overhang length using different sets of process parameters. Visual inspection, three-dimensional scanning, and metallographic inspection of the cross-sections were performed. A quality control methodology based on dimensional and geometric tolerances has been defined in order to quantitatively characterize the quality of the struts. Optimized process parameters were selected and used to fabricate octet-truss specimens which were then characterized by compression testing.